IMPROVEMENT OF TACTICAL APPROACHES IN THE TREATMENT OF DESTRUCTIVE FORMS OF ACUTE PANCREATITIS - Murod Sh.Khakimov; Maxmud R.Karimov; Bekzad B. Fayzullaev; Azizbek F.Valijonov; Shirina A. Valijonova (Scholar Express Journals, 2022)
Despite the rapid development of medical science and technology, the issues of diagnosis and treatment of destructive forms of acute pancreatitis remain one of the complex problems of modern urgent surgery. The frequency of this disease increases from year to year, and in the structure of abdominal urgent surgery, this pathology occupies a leading place, and in terms of growth rates, it is ahead of all other emergency abdominal diseases. It should be noted that along with the increase in the absolute number of patients, there is an even greater tendency to the growth of destructive forms. In Uzbekistan, according to the Institute of Health and Medical Statistics, more than 600 operations for pancreatic necrosis are performed annually in the country. At the same time, postoperative mortality in some regions reaches 28.6-30.8%
Keywords: Destruction; sequestration; pancreatic necrosis; pancreatitis